Design and development of a methanol concentration controller for fuel cells - Viljoen, Marius (My University, 2010)
The demand for higher efficiency, sustainability and cleaner power sources increases daily. A Direct Methanol Fuel Cell is a power source that can be applied for small to medium household appliances and office equipment. It can ideally be used for operating appliances like notebook computers on remote sites where no electrical power is available. One of the problems in methanol fuel cells is methanol crossover. Methanol crossover occurs when methanol is not completely used in the process of generating electrons, and a certain percentage of the methanol is wasted. Crossover may damage the proton exchange membrane of the fuel cell and reduce the efficiency of a DMFC. Literature reviews were done and suggestions from other writers are discussed on how to reduce methanol crossover. This research focuses primarily on the fact that crossover can be controlled by controlling the methanol / water concentration. A prototype methanol controller was built with an ultrasonic sensor for detecting the density of the methanol/water mixture and a sensor for the temperature of the mixture; this was done because the density of the mixture is dependant on the temperature and the concentration. The controller was calibrated to determine the amount per volume of water and methanol which enables the controller to control the percentage of methanol in the water. The prototype also had the feature built in to adjust the mixture in order to enable the study on the effects of crossover. A data logger function was added to store collected data on a personal computer for the study on methanol and water. It was observed that the sensor was sensitive enough and was able to produce 1% increments of the level of methanol concentration in the water provided the temperature was stable. A methanol controller was successfully built to ensure the correct volume of methanol.
Thesis (M. Tech.) (Engineering: Electrical, Dept.: Electronic Engineering))--Vaal University of Technology, 2008.
Keywords: Power sources; Household appliances; Methanol concentration controller; Direct methanol fuel cell; Methanol crossover; Methanol/water concentration; Methanol and water; Methanol controller; Fuel cells